Distribution Information System at Rani Motor Workshop with DRP Method to Improve Sparepart Delivery Timeliness - Gunawan, Haris; Fakhriza, Muhammad (Sistemasi: Jurnal Sistem Informasi, 2024)
Rani Motor Workshop in North Sumatra faces several problems in its operations, such as inefficient inventory management, late delivery of spare parts, and unstructured distribution planning. This research aims to overcome these problems by integrating the Distribution Requirement Planning (DRP) method in its distribution information system using a research and development (R&D) approach and a waterfall development model. By detailing the flow of data input, distribution planning, parts delivery, and distribution performance recording, this research proposes a framework that integrates the research & development method and the waterfall system development method. Through these steps, this research aims to improve the efficiency and timeliness of delivery. The results of this research are expected to make a positive contribution to the operations of Bengkel Rani Motor, by proving that the implementation of a distribution information system using the DRP method can optimize stock, reduce delays, and increase customer satisfaction.